Manajemen Kepala Madrasah dalam Meningkatkan Rekrutmen Peserta Didik di MI Roudlotul Ulum Kecamatan Mojosari Kabupaten Mojokerto - Anang Budi Cahyono; Amru Almu’tasim; Ashari Ashari (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2023)
This research uses a qualitative descriptive case study type approach. Data collection techniques using observation, interviews and documentation. Data analysis from the results of observations, interviews and documentation begins with data reduction, data presentation and ends with drawing conclusions.The results of this study are: 1) Management of Head Masters in increasing the recruitment of new students starts with a work plan that is formulated from objectives based on the school's vision and mission. The principal has three principles that the first principal can do; planning, the second; announcement of information, the third; file selection, 2) Implementation management of Head Masters in the recruitment of new students takes organizing actions to create a good new student committee structure, in application through three processes namely planning, information announcement, file selection.